Pengaruh Cotrimoxazole Terhadap Perkembangan Neural Tube Embrio Ayam - Pamuji, Alifia Shafanaura; Fauziah, Cut; Tjang, Yanto Sandy; Thadeus, Maria Selvester (Jurnal Biomedika dan Kesehatan, 2024)
Background In Indonesia, congenital abnormalities are still very high. Neural Tube Defect (NTD) is one of the most common congenital abnormalities. NTD occurs due to the failure of neural plate closing. One of the risk factors for NTD is folic acid deficiency. Drug use during pregnancy is one of the risk factors for congenital abnormalities. Cotrimoxazole is an anti-folate drug that still has pros and cons regarding its potential to cause NTD. Human embryonic brain development can be simulated using chicken embryos. This study aimed to determine the effect of Cotrimoxazole on the development of the chicken embryo's neural tube. Methods This study used a post-test-only control group design. The number of samples is 30 eggs and the sampling method was simple random sampling. The dose of Cotrimoxazole used was 0; 60; and 120 mg/kg per egg then the eggs were incubated for 72 hours. Data analysis was based on sample characteristics and bivariate analysis using the comparative Kruskal-Wallis test with the post-hoc test. Results In this study, 11 out of 30 eggs could be analyzed. The results were obtained by observing the number of brain vesicles. There was a significant difference in the number of brain vesicles (p= 0.046) between the study groups from the Kruskal-Wallis test. Conclusions Cotrimoxazole administration showed an effect on neural tube development of chicken embryos when compared to controls.